Metanephric adenoma of kidney: a rare and distinct entity - Patil, Purwa; Bhatia, Varsha; Arole, Vidya; Thakare, Nisha (International Journal of Research in Medical Sciences, 2016)
Metanephric adenoma (MA) is an unusual renal neoplasm with benign behaviour most of the times. Clinically MA mimics malignant renal neoplasms due to nonspecific signs and symptoms such as polycythaemia, haematuria and abdominal pain. MA usually presents as a mass lesion on radiographic studies and can be found incidentally. The treatment of choice is surgical excision. Though MA is usually a benign tumour, increase in the knowledge of MA pathology may lead to less invasive treatments in the future. Less than 200 cases of metanephric adenoma are reported till date in the literature.